Posttraumatic Stress Disorder Symptom Trajectories in ICU Family Caregivers. (26th April 2021) - Wendlandt, Blair; Chen, Yi Tang; Lin, Feng-Chang; Toles, Mark; Gaynes, Bradley; Hanson, Laura; Carson, Shannon
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To use latent class growth analysis to identify posttraumatic stress disorder symptom trajectories in ICU family caregivers. Design: Prospective cohort study. Setting: The medical ICU at a tertiary-care center in the United States. Participants: Adult patients experiencing acute cardiorespiratory failure (defined as requiring at least one of the following: 1) vasopressors, 2) noninvasive positive pressure ventilation, 3) high-flow nasal cannula, or 4) mechanical ventilation) were enrolled in a pair with their primary family caregivers. Measurements and Main Results: Participants were enrolled within the first 48 hours of ICU admission. Family caregiver posttraumatic stress disorder symptoms were measured using the Impact of Events Scale-Revised at four time points: at enrollment, shortly after ICU discharge, and at 3 and 6 months after ICU discharge. The data were examined using latent class growth analysis to identify posttraumatic stress disorder symptom trajectories. Two distinct symptom trajectories were identified: a persistently high trajectory, characterized by high posttraumatic stress disorder symptoms at initial assessment, which remained elevated over time, and a persistently low trajectory, characterized by low posttraumatic stress disorder symptoms at initial assessment, which remained low over time. Approximately two-thirds of caregivers belonged to the persistently high trajectory, and one-third of caregivers belonged to the persistently low trajectory. Conclusions: Using latent class growth analysis to measure 6-month ICU family caregiver posttraumatic stress disorder symptom trajectories, we identified two distinct trajectories (persistently low and persistently high). A larger cohort study is warranted to further delineate posttraumatic stress disorder trajectories in this population, with the ultimate goal of targeting high-risk caregivers for interventions to reduce psychologic distress and improve long-term caregiver outcomes.